(untitled) (Archives of Criminology, 1991)
The Surveys Since 1961, nine alcohol consumption surveys were carried out on the national level in Poland. The interests of their authors, the contents of questionnaires, and the ways of conducting the surveys varied, but most of them exhibited some common features. First of all, the respondents were met personally by the interviewers who filled up the questionnaires during the interview. Most of the surveys were based on quota samples of adult population, but in some also youngsters aged over 15 or 16 were included into the sample. The last occasion approach prevailed in the surveys; in one of them only, the respondents were asked to describe their last three drinking occasions. In some surveys, the respondents were also requested to estimate the frequency of their drinking of spirits during the last three months. In the present paper, some findings of the fifth and seventh surveys are analysed. The two surveys were carried out in 1980 and 1985, respectively. The estimate of frequency of drinking spirits derived from answers to the questions related to drinking during the last three months and to those about the last drinking occasion proved to differ markedly in exceptional cases only. However, as expected, the last occasion approach produced somewhat higher estimates of consumption level than that based on the respondent’s appraisal of the frequency of his or her own drinking during the last three months. The coverage rate was similar in both surveys: 47 per cent in 1980 and 56 per cent in 1985, and its level is in accordance with the findings obtained in surveys carried out in other countries. The Questions The questionnaires of both surveys included several questions related to positive and negative experiences the respondents had had as a result of their drinking. The proper part of the questionnaire used in the 1980 survey was of an experimental character. Its main aim was to collect data on the issue neglected in the Polish literature, i.e. on rewards resulting from drinking alcohol. In the literature in question, much attention had been paid to the detrimental consequences of drinking as if they were the only ones. The assumption that drinking has also some positive value for alcohol consumers seemed plausible: why would they otherwise drink at all? The questions asked were not intended to reveal what really happened to the persons who consume alcohol, but rather to get some insight in to the way they perceived occurrences which they rightly or mistakenly attribute to their drinking of alcohol. What seemed interesting were also the spheres of life in which alcohol played a positive as opposed to a negative role. As that part of the questionnaire was of an exploratory nature only, the respondents were asked about events in which alcohol helped them somehow or caused them getting into trouble, whenever that occurred. In the questionnaire of the 1985 survey, more attention was paid to the wording of those questions. Firstly, the respondents were asked about occurrences which had happened during the last twelve months preceding the interview. That was the time limit introduced in order to separate drinkers from non-drinkers, and in that case also to distinguish the “current” from the past events. Secondly, in the case of a good as well as bad experience, the types of occurrences in question were both of a trivial character and of such a nature that they could be related to a single drinking occasion. Thirdly, in reration to some spheres of life questions, about both positive and negative consequences were asked. Some of the questions included in the 1980 and 1985 questionnaires were formulated the way adopted in the Scandinavian Drinking Survey of 1979 which was carried out in Finland, Iceland, Norway, and Sweden. Similar questions were also asked in Finnish surveys conducted in 1968, 1976, and 1984. The Polish, the Scandinavian, and the Finnish surveys, were carried out at different times, in different manners, and on differently drawn sampres. Therefore, it would be impossible to compare, their findings directly. However, it seems interesting to point to some most striking discrepancies between them as a point of departure for theorizing on possible differences in the role played by alcohol in social life in Poland and in the Scandinavian countries. The Findings The main findings of the inquiry qan be summarized as follows: As could be expected, asking about events which might have occurred at any time in the respondents’ life has led to a higher proportion of positive answers as compared to asking about events that occurred during the last twelve months. In the Polish surveys, this could be noticed in the case of sorting out probrems related to people close to the respondent (49.7 and 21.7 per cent, respectivery), of taking a more, optimistic view of life (40.8 and 18.7 per cent, respectively) and in several other questions, while in the case of the Finnish surveys, in relation to being picked up by the police for being drunk (8.5–10.9 and 3.5 per cent, respectively). This observation is fairly obvious and has been mentioned here only to support confidence in the findings obtained. The questions included in the questionnaire of the 1980 Polish survey were formulated in a manner that was not too well suited for comparisons between the positive and negative experiences stemming from drinking. However, they provided some clues for supposing that good experiences occur more often than bad ones. The evidence provided by the answers in the l985 survey clearly supports this assumption. First of all, the prevalence of an experience is related to its type. The most common ones were: being more resolute in company, and spending more money than one otherwise would (it happened to 36.2 and 34.9 per cent of drinkers, respectively, during the last twelve months). It shows that positive as well as negative experiences related to drinking may be quite common. Most revealing are the answers to questions that pertain to similar types of events. There were four times more drinkers who felt that because of alcohol they were more resolute in company than those who acted as spoil-sports in company because of their drinking (36.2 as opposed to 8.3 per cent, respectively); three times more respondents who sorter out problems connected with their job with the help of alcohol than those who had some trouble at work because of their drinking (23.8 as opposed to 6.7 per cent, respectively); distinctly more sorted out problems related to people close to them than spoiled their relations with such persons (21.7 as opposed to 14.8 per cent, respectively); and finally, many more respondents took an optimistic rather than a pessimistic view of life because of drinking (18.7 as opposed to 10.4 per cent, respectively), It shows definitely that positive consequences of their own drinking are noticed by far more persons than the negative ones. The above findings concern the distribution of answers obtained from all drinkers in the sample. However, they do not preclude the contents of individual respondents’ answers. Are there two separate groups of drinkers: one consisting of those who have positive experiences with drinking, and another one, distinctly smaller, made up of those who have negative experiences related to the use of alcohol? Or is there one group only: the same people have good and bad experiences with drinking, the good ones prevailing in most cases? None of these alternatives appeared to be fully substantiated by the findings of the 1985 survey. First of all, more than two in five of the drinkers reported none of the good experiences listed, and more than one in two – none of the bad experiences. Thus there is a third (or a second) group of respondents drinking alcohol, viz. those who have neither positive nor negative experiences with it. Hence the possible concurrence of good and bad experiences related to drinking may be found in about a half of the drinkers only. All types of good and bad experiences were positively correlated with all types of bad experience listed in the questionnaire (X2 = from 87.8 to 274.3; df = 4; p < T = from 0.17 to 0.32). This points clearly to the second of the above alternatives, viz. to the view that those were predominantly the same persons who admitted having had both good and bad experiences related to drinking. Formulating this observation differently, one might say that having some good experience with drinking enhances the likelihood of having also bad experience with alcohol, and vice versa. In order to proceed further in this analysis, two indices were calculated. Both of them are related to variety and not quantity of experiences, as the questionnaire of the 1985 survey did not contain questions about how often the separate types of experiences listed had occurred. To form the index of good experiences, the number of “yes” answers was calculated, and accordingly the respondents received scores from 0 (no “yes” answers) to 7 (“yes” answers to all types of experiences quoted). The index of bad experiences was formed similarly. The mean score was 1.65 for positive experiences and 1.12 for the negative ones which shows once more that the incidence of the first kind of experiences prevailed over the other one. As it has already been mentioned, quite a number of respondents gave no “yes” answers at all. On the other end of the scale, there were relatively few persons who gave five or more “yes” answers; in the case of good experiences, there were 11 per cent of such persons, and in the case of bad ones – 5 per cent only. The close relationship between having good as well as bad exaperiences is demonstrated by the mean scores of index of good experiences related to drinking calculated for every level of the index of bad experiences, and vice versa. The picture shown by those scores is quite clear: the higher the number of positive types of experiences related to the use of alcohol, the higher also the number of negative experiences stemming from drinking. The same is also true for negative experiences: the greater their number, the more numerous also positive experiences. In conclusion it can simply be said that the drinkers who believe that alcohol drinking is rewarding are generally also aware of some unpleasant consequences which follow its use, and vice versa. A closer look at the scores of both indices revealed that on every level of the index of positive experiences, the number of those experiences exceeded markedly that of the negative ones (the only exception found is in the case of no positive experience). A partly similar picture emerges while looking at the consecutive levels of negative experiences: in the lower part of the scale, mean numbers of positive experiences surpass those of negative ones; only in the case of those respendents who reported four or more types of negative experiences, the numbers of positive experiences were smaller. Finally, the question arises how could this concurrence of good and bad experiences be explained. Or, to take a different approach, what, if anything, distinguishes the respondents who admit having many types of positive and negative experiences from those who do not happen to have them at all or who have a few only. The answer is again surprisingly simple. What seems to determine the number of experiences related to drinking is the level of alcohol consumption. In the case of the Polish drinking habits, this means practically the level of consumption of spirits. The greater the number of types of negative or positive experiences, the higher the consumption level of alcohol (spirits). In persons who reported no good or bad experiences related to drinking, mean alcohol consumption was less than a half of the average. With a rise in the number of types of positive and negative experiences stemming from drinking, the amount of alcohol consumed is also rising steeply to a level more than twice as high as the average for all drinkers. It has also to be stressed that the conusumption level associated with the same number of types of negative experiences related to drinking is higher than in the case of positive ones. Looking at this relationship at the background of the level of consumption, it can be stated that e.g. those who drunk ten to eleven litres of spirits yearly have had one type of bad and two types of good experiences related to the use of alcohol; those who drunk seventeen to twenty litres had two to three types of bad and three–four types of good experiences; and those who drunk about twenty-five litres of spirits yearly had four types of bad and five types of good experiences stemming from alcohol. The predominance of positive experiences is present all the time; however, it tends to get smaller with the increase in consumption level. The description of respondents who tended to have more good and bad experiences related to drinking corresponds strictly to that of those who are drinking more than others. Over-represented are among them: men, middle-aged, having primary education only or unfinnished secondary school, having, blue-collar jobs, describing themselves as nonbelievers or non-practising believers, having disputes and arguments with their families, with neighbours, friends, colleagues and superiors at work, having often the feeling of not enjoying the esteem they deserve. Conclusions For most Poles who drink alcohol, drinking does not seem to be associated with any particular experiences of a positive or negative value. They do not drink much, do it occasionally, probably mostly for social reasons. For those who drink more than the average and, in particular, for those who drink heavily, alcohol consumption tends to be associated with some good or bad experiences which they relate to their use of alcohol. The more they drink, the more experiences of both kinds they have. However, experiences of a rewarding nature prevail over consequences that are annoying or unpleasant. While looking at similar Scandinavian surveys, some striking differences in the incidence of types of occurrences related to drinking can be noticed. In Poland, alcohol seems to serve much more often than in the Scandinavian countries as a means of sorting out problems the drinking person has with people close to him, and in particular, in sorting out his or her problems at work. On the other hand, as far as the use of alcohol for acquiring some psychological effects is concerned (such as improving the mood, better expressing one’s feelings, or saying something one regrets afterwards), the Poles do not seem to differ much from the Scandinavians, particularly from those who are ress successful in this sphere. The Poles seem to have also more health problems related to drinking, even in comparison to those Scandinavians who drink mostly spirits, like the Icelanders.